1997
DOI: 10.1007/bf02480370
|View full text |Cite
|
Sign up to set email alerts
|

Insect circadian rhythms and photoperiodism

Abstract: Two clock-controlled processes, overt circadian rhythmicity and the photoperiodic induction of diapause, are described in the blow fly, Calliphora vicina and the fruit fly, Drosophila melanogaster. Circadian locomotor rhythms of the adult flies reflect endogenous, self-sustained oscillations with a temperature compensated period. The free-running rhythms become synchronised (entrained) to daily light:dark cycles, but become arrhythmic in constant light above a certain intensity. Some flies show fragmented rhyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 51 publications
0
33
0
1
Order By: Relevance
“…The use of daylength cues allows organisms to track time of year and to anticipate predictable annual variations in environmental signals. An accurate photoperiodic perception is essential in maintaining appropriate clock-dependent phase relationships with the external day/night cycles (Saunders, 1997;Oster et al, 2002;Johnson et al, 2003;Merrow et al, 2006). Plants also use the circadian clock to perceive the changing photoperiods and to synchronize gene expression and physiology to the most favorable seasons (Má s, 2005;McClung, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The use of daylength cues allows organisms to track time of year and to anticipate predictable annual variations in environmental signals. An accurate photoperiodic perception is essential in maintaining appropriate clock-dependent phase relationships with the external day/night cycles (Saunders, 1997;Oster et al, 2002;Johnson et al, 2003;Merrow et al, 2006). Plants also use the circadian clock to perceive the changing photoperiods and to synchronize gene expression and physiology to the most favorable seasons (Má s, 2005;McClung, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between these two phenomena is still largely unresolved. Formal properties of photoperi odic responses indicate that photoperiodic time measure ment is a function of the circadian system (Saunders, 1998;Vaz Nunes & Saunders, 1999). Recently, Veerman (2001) suggested that downstream events, such as syn thesis of a clock substrate, are under circadian control in insects and mites.…”
Section: Introductionmentioning
confidence: 99%
“…Obligatory diapause occurs at a specific stage in the life cycle irrespective of prevailing environmental conditions, while facultative diapause is induced following detection of specific environmental cues (Denlinger, 2002). The dominant induction cue is day length (photoperiod), which has provided a robust indicator of approaching winter conditions throughout evolutionary time (Saunders, 1997;Saunders, 2013). Induction occurs during a sensitive stage in the life cycle, and the critical day length (CDL) denotes a photoperiod that induces 50% diapause within a population (Tauber et al, 1986).…”
mentioning
confidence: 99%